A distance sampling survey of the Critically Endangered Straw-headed Bulbul Pycnonotus zeylanicus in Singapore. Issue 3 (16th September 2021) - CHIOK, WEN XUAN; NG, ELIZE Y. X.; TANG, QIAN; LEE, JESSICA G. H.; RHEINDT, FRANK E.
Summary: The Straw-headed Bulbul Pycnonotus zeylanicus is one of South-East Asia's most threatened songbirds due to relentless demand for the regional cage-bird trade. The species was recently uplisted from 'Endangered' to 'Critically Endangered' only two years after its previous uplisting. Intriguingly, populations in highly urbanised Singapore appear relatively secure. However, the last Singaporean density estimates, derived from traditional census methods, were obtained nearly two decades ago in 2001. A recent population estimate in 2016 was derived from the census work in 2001 coupled with relative abundance indices from population trends. We thus performed systematic field surveys using the distance sampling method, estimating 573 ± 185 individuals nation-wide, with a break-down of 217 ± 81 on the main island of Singapore and 356 ± 104 birds on the satellite of Pulau Ubin. Taken together, the total population estimate reported here comprises 22.9–57.3% of the global wild population, underscoring the importance of Singapore as a stronghold for the species. In spite of its apparently secure status in Singapore, the species remains susceptible to local and foreign trapping pressures. Based on our assessment, we propose a number of local and regional conservation measures to ensure the continued survival of populations in Singapore.